Synthesis and evaluation of N-alkylated analogues of aza-galacto-fagomine – potential pharmacological chaperones for Krabbe disease. Issue 36 (22nd August 2016) - Viuff, Agnete H.; Jensen, Henrik H.
Abstract : Seven novel alkylated or acylated analogues of hexahydropyridazine aza-galacto-fagomine (AGF) was prepared and studied as glycosidase inhibitors with the aim of increasing inhibitory potency and selectivity. Abstract : Seven novel alkylated or acylated analogues of hexahydropyridazine aza-galacto-fagomine (AGF) was prepared and studied as glycosidase inhibitors with the aim of increasing inhibitory potency and selectivity. The enzyme galactocerebrosidase, implicated in Krabbe disease, was found to be potently inhibited by n -butyl N 2-alkylated AGF.